Acceptability and feasibility of intra-peer and social media approach for HIV self-testing among men who have sex with men in Karachi: lessons from a pilot study - Arshad Altaf; Pasha, Muhammad Safdar Kamal; Siddiqui Wali, Muhammad; Majeed, Ayesha (Journal of the Pakistan Medical Association, 2023)
Objective: To use a peer-to-peer and social media approach to reach out to men who have sex with men and to distribute human immunodeficiency virus self-testing kits among them in an urban setting. Method: The cross-sectional, pilot study was conducted by a community-based organisation in Karachi from November 2020 to February 2021, and comprised men aged 18 years or above who have sex with men. The subjects were provided one human immunodeficiency virus self-testing kit per person by trained outreach workers. It was an oral fluid-based kit. Data related to demographics, behavioural patterns and human immunodeficiency virus testing detail was collected on a structured questionnaire with some open-ended questions. The analysis of qualitative data was done manually, using content analysis technique in which all common responses were grouped that led to the generation of themes. Results: There were 150 male subjects with mean age 31.5+/-8.7 years. Overall, 62(41.3%) subjects had received up to 15 years of formal education, 94(62.6%) were first-time testers; 139(92.7%) performed the test at home; 11(7.3%) used the kit at the community-based organisation’s office. In terms of results, 1(0.7%) participant had a reactive result which was later confirmed as positive for human immunodeficiency virus. Of the total, 145(96.6%) participants found the instructions and the kit easy to use on their own, 83(55.3%) preferred a social media-based approach, and 68(45.3%) preferred the peer-to-peer approach. Conclusion: The human immunodeficiency virus self-testing kit was found to be acceptable among men who have sex with men, while peer-led and social media approaches seemed to be an effective method of information dissemination. Key Words: HIV testing, HIV self-testing, Pilot study, HIV Pakistan, Men who have sex with men, Peer to peer, Social media.